Rendimento produtivo e econômico de frangos isa label alimentos com rações contendo farelo de girassol - Silva, Ligiane Nadja Souza (Universidade Federal Rural do Semi-Árido, 2013)
Considering the prevalence of soybean s bran in chickens ration and its valorization, other agroindustrial subproducts with protein characteristic, for instance, sunflower s bran, has been purposed in feeding programs. Therefore, aiming to evaluate protein s source s replacement in balanced rations over productive and economic yield of Isa Label s chickens in semi-intensive system, 320 birds were selected between 28 and 35 days-old and monitored until 121 days-old, being destined to conventional slaughter subsequently. The dietary treatments were constituted in a reference ration with soybean meal (RFS) and three other rations with gradual levels of replacement of soybean meal by sunflower meal with basis in the protein of these ingredients, in levels of 15% (FG15), 30% (FG30) and 45% (FG45), properly supplied with lysine and methionine. Such rations has suffered nutritional adjusts according to the growing phase, namely, period 1 (35 to 63 days), period 2 (64 to 92 days) and period 3 (93 to 121 days). There weren t observed any significant differences of the birds performance during the growing phase in function of dietary treatments, determining the following general averages to the periods 1, 2 and 3: feed intake in 108,08 ; 139,25 and 165,80 grams/day; weight gain in 44,32 ; 43,15 and 28,43 grams/day; and food conversion 2,50; 3,56 and 6,21 kg/kg, respectively. The protein replacement of soybean by sunflower in Isa label chickens ration didn t influence significantly either the yield carcass, the cuts and eatable visceral. These parameters presented general averages of 74,29% to carcass yield, of 19,33% to breast, of 12,55% to thigh, of 11,56% drumstick, of 0,47% to heart, of 1,24% to liver and of 1,68% to gizzard. The economic analysis demonstrated the reduction in financial value per kilogram of ration in proportion to the replacement in 15, 30 and 45% of the soybean meal by sunflower meal with basis in protein content and supplemented with lysine and methionine (R$1,77, 1,75, 1,70 and 1,67, respectively) and elevation of profitability index in function of sale s price of the chicken carcasses (R$ 2,44, 2,40, 2,57 and 2,58, respectively). Thus, the additional profit and the balance price were favored by the inclusion of sunflower meal in balanced rations to Isa Label chickens in semi-intensive production system
Productive and economic performance of chickens isa label foods diets containing sunflower meal
Keywords: chicken; performance; Annuu Helianthus; protein; Aves; Desempenho; Helianthus annuu; Proteína; CIENCIAS AGRARIAS::MEDICINA VETERINARIA